First Impression- the Component of Social Perception - Mocanu, Lacramioara (Didactica Danubiensis, 2023)
Social life involves a permanent interaction with others. The quantity of information goes secondary in relation with the importance of our impression about the other. The manner in which each individual creates a personal image for their peers, more or less complete, in accordance with reality, is a part from what they call social perception.